Edukasi Kontrasepsi IUD pada Akseptor KB di Rt. 9 Kelurahan Pasar Lama Wilayah Kerja Puskesmas S.Parman Kota Banjarmasin - Husnul Khatimatun Inayah; Netty Netty; Nurul Indah Qariati; Ari Widyarti (Jurnal Abdimas Kesehatan (JAK), 2020)
AbstractThe total population of Indonesia in 2016 was 258,986 people with a population increase of 3.24 million people per year. The efforts of the government to reduce the rate of population growth by the number of births through the Family Planning program and to maintain the age of first marriage. The most dominant contraceptive method in Indonesia is the short-term contraceptive method, namely injections (52.8%) and pills (23, 77%). Whereas Contraception in the Womb or IUD (IUD) (4.73%), which has good effectiveness and long term contraception is in great demand. Low IUD allocation. External and internal factors. internal factors include incorrect knowledge about the IUD and low education. The target of education is the mother of acceptors in RT 9 Kelurahan, Pasar Lama, working area in the Puskesmas S. Parman, Banjarmasin. Where active KB acceptors are 38 people, who use contraceptive pills 20 people, injections 18 people, condoms and IUDs were absent during 2018 and January - August 2019, active KB acceptors 39 people, who used contraceptive pills 21 people, injections 18 people, condoms and the IUD does not exist. The purpose of this activity is to increase the knowledge of family planning acceptors about contraception in general and IUD contraception in particular. The method used is an explanation using flipcharts and questions and answers. As a result of community service activities, an increase in knowledge about IUD contraception occurred.